Recognizing the Referent - Valdivia, Lourdes (2015)
In this article I show that in a trivial way, as Glezakos holds, there is no puzzle. However, this is the case only when no theoretical assumptions are made. I argue that the puzzle can be posed independently of the sense/reference distinction by trying to answer a theoretical question about the relation between the meaning and the epistemic profiles of identity statements. Contrary to Glezakos I claim that it is possible to attach different epistemic profiles to each identity schema. As I read the puzzle it may be a problem for those who hold that meaning is explained by reference and accept the epistemic profiles of the two schemas.